1997
DOI: 10.1038/sj.ejcn.1600363
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of energy intake estimated by a diet history in three free-living 70 year old populations in Gothenburg, Sweden

Abstract: Objective: To evaluate the credibility of estimates of energy intake from a Diet History (DH) by cut off limits for the multiple of energy intake and basal metabolic rate (EI/BMR est ) and by physical activity levels (PAL, total energy expenditure TEE/BMR). Design: Cohort study. Setting: Departments of Geriatric Medicine and Clinical Nutrition, Göteborg University, Gothenburg, Sweden. Subjects: 369 males and 440 females from three representative cohorts of free-living individuals from the gerontological and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 38 publications
3
24
3
Order By: Relevance
“…This procedure, known as the Goldberg cut-off technique, has demonstrated a widespread tendency to underestimation in large national dietary surveys from several countries as well as in many smaller surveys (Heywood et al, 1993;Fogelholm et al, 1996;Briefel et al, 1997;Lafay et al, 1997;Price et al, 1997;Pryer et al, 1997;Rothenberg et al, 1997;Voss et al, 1998). However, this technique was devised to evaluate the overall bias towards under-reporting at the group level.…”
Section: Introductionmentioning
confidence: 99%
“…This procedure, known as the Goldberg cut-off technique, has demonstrated a widespread tendency to underestimation in large national dietary surveys from several countries as well as in many smaller surveys (Heywood et al, 1993;Fogelholm et al, 1996;Briefel et al, 1997;Lafay et al, 1997;Price et al, 1997;Pryer et al, 1997;Rothenberg et al, 1997;Voss et al, 1998). However, this technique was devised to evaluate the overall bias towards under-reporting at the group level.…”
Section: Introductionmentioning
confidence: 99%
“…Although results from most studies consistently show that underreporting is more likely in obese subjects, it is also evident that obese subjects do not necessarily underestimate energy intake (Bandini et al, 1990;de Vries et al, 1994). Normalweight subjects were also among the underreporters and underreporting may be related to other factors as well (Fogelholm et al, 1996;Pryer et al, 1997;Rothenberg et al, 1997). Independent of the individual characteristics that were related to underreporting, underreporting is observed in many dietary studies and raises the question about the quantity and the quality of non-reported components of the diet.…”
Section: Discussionmentioning
confidence: 99%
“…In a Finnish study, reported energy intakes below cut-off 1.28 were seen in 42% of the men and 47% of the women (Fogelholm et al, 1996). Rothenberg et al (1997) found more than 50% of subjects reporting energy intakes below a ratio EIaBMR of 1.52 in a cohort of 70 y old Swedish men and women. In the present study the overall mean EIaBMR of 1.47 for men and 1.49 for women was close to the average value of 1.55 for men and 1.56 for women suggested by FAOa WHOaUNU (1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 63 % of groups mean EI was more than 10 % below mean EE and in only one group was it more than 10 % above EE. Comparisons of EI expressed as a multiple of BMR (EI : BMR) with the physical activity level (PAL) for a sedentary lifestyle have confirmed the widespread tendency to underestimation of EI in large national dietary surveys from several countries (Heywood et al 1993;Klesges et al 1995;Ballard-Barbash et al 1996;Fogelholm et al 1996;Briefel et al 1997;Lafay et al 1997;Price et al 1997;Pryer et al 1997;Rothenberg et al 1997;Braam et al 1998;Gnardellis et al 1998;Voss et al 1998) and also many smaller studies. Mean reported EI : BMR values were predominantly in the range of 1⋅2-1⋅5, whereas DLW studies suggest that EE is greater than 1⋅55 × BMR in all age groups except those aged over 75 years .…”
mentioning
confidence: 86%